2009
DOI: 10.1128/jvi.00889-09
|View full text |Cite
|
Sign up to set email alerts
|

Human VAP-C Negatively Regulates Hepatitis C Virus Propagation

Abstract: Human vesicle-associated membrane protein-associated protein (VAP) subtype A (VAP-AHepatitis C virus (HCV) is a major causative agent of chronic liver disease and thus a major public health problem, infecting at least 3% of the world population (47). HCV infection proceeds to the persistent stage in approximately 80% of patients, leading to the development of cirrhosis in 20% to 50% of patients, of whom approximately 5% eventually develop hepatocellular carcinoma (12). HCV encompasses a single-stranded positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 53 publications
1
20
0
Order By: Relevance
“…8A and B). It has been reported that several host cofactors involved in HCV replication, such as chaperonin TRiC/CCT, VAP-A, VAP-B, and PI4KIII␣, are recruited into the membranous HCV replication compartment by HCV replicase proteins (25,32,33,41,42). Taken together with our findings, the evidence to date emphasizes a common strategy in which HCV recruits host proteins into the membranous HCV replication compartment by replicase proteins to regulate its replication.…”
Section: Discussionsupporting
confidence: 75%
“…8A and B). It has been reported that several host cofactors involved in HCV replication, such as chaperonin TRiC/CCT, VAP-A, VAP-B, and PI4KIII␣, are recruited into the membranous HCV replication compartment by HCV replicase proteins (25,32,33,41,42). Taken together with our findings, the evidence to date emphasizes a common strategy in which HCV recruits host proteins into the membranous HCV replication compartment by replicase proteins to regulate its replication.…”
Section: Discussionsupporting
confidence: 75%
“…[146][147][148] This hypothesis is supported by the aberrant fractionation of NS5B in detergent soluble membranes and by the decreased HCV replication upon VAP-A and -B silencing or overexpression of dominant-negative VAPs. [146][147][148][149][150] Whether VAP-C also contributes to HCV replication remains to be confirmed, 149 as this protein is not expressed in liver tissue. The VAP-A-NS5A interaction appears to depend on the phosphorylation status of the viral protein.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…VAP-C is a splicing variant of VAP-B that lacks two thirds of the C terminus [36,37] ; therefore, it cannot interact with VAP-A, VAP-B or NS5A. A physiological role of VAP-C was recently demonstrated by Kukihara et al [38] , who found that VAP-C inhibited the association between VAP-A/B and NS5B, thereby reducing HCV replication efficiency. Interestingly, VAP-C expression in hepatocytes was found to be negligible, which may be advantageous for and CHC patients (n = 3) were subjected to SDS-PAGE and analyzed by immunoblotting using anti-IRF-3 and anti-ACTB antibodies.…”
Section: Vap-c Expression In B Cellsmentioning
confidence: 94%
“…VAP-B has been identified as another NS5A-binding protein by screening human libraries using the yeast two-hybrid system with NS5A as bait [35] . Both VAP-A and VAP-B are involved in HCV replication via interactions with NS5A and NS5B [35] , while VAP-C inhibits the association between VAP-A/B and NS5B, which results in reduced HCV replication efficiency [38] . Therefore, the absence of VAP-C expression in B cells, similar to hepatocytes, may be favorable for HCV replication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation